PENGENAAN PAJAK PENGHASILAN FINAL BERLAPIS TERHADAP PENGALIHAN HAK ATAS TANAH DAN/ATAU BANGUNAN BAGI PEMOHON HAK BARU DI KABUPATEN DELI SERDANG - ROOSMIDAR ROOSMIDAR (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Utary Maharany Barus3. Bastari Someone who requests for new right on uncertified land and building (the first Registration) in the Land Office of Deli Serdang Regency has to pay for BPHTB and stratified PPh Final PHTB according to the chronology of the amount of land and/or building right transfer. The title of the research is “Imposition of Stratified Final Income Tax on Land and/or Building Right Transfer for an Applicant of New Right in Deli Serdang Regency.” The problem formula is as follows: what type of tax imposed on an applicant of new right of land and/or building in Deli Serdang is, how about fulfilling the principle of legal certainty in the regulation on the imposition of stratified PPh Final PHTB of PPJBTB on a new applicant of new right in Deli Serdang, and how about the fulfillment of the principle of justice in the regulation on the imposition of stratified PPh Final PHTB of PPJBTB on a new applicant of new right in Deli Serdang.Keywords: Tax, Request for New Right, Deli Serdang